Pengaruh Model Pembelajaran Savi Berbantuan Media Roda Putar Bangun Ruang Terhadap Hasil Belajar Siswa Kelas V SDN 2 Fontein Kota Kupang - Aksalinda Baitanu; Cornelia A. Naitili; SiprianusTua (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Baitanu Aksalinda, 2025, The Effect of SAVI Learning Model Assisted by Rotating Wheel Media on the Learning Outcomes of Grade V Students of SDN 2 Fontein, Kupang City, Thesis of Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University. Supervisor 1 Cornelia A, Naitili, S.Pd., M.Pd and Supervisor II Siprianus Tua, S.Pd., M.Pd. The SAVI learning model is one of the learning models that adheres to the modern cognitive flow by stating that good learning activities involve emotions, physical movements or sensory organs and intellectual activities, and respect the differences in learning styles of each student. So that in learning that is in accordance with the Savi learning theory in accordance with the main objective of mathematics learning, namely to help develop the knowledge, attitudes and skills of students. The purpose of this study is to determine the effect of the SAVI learning model assisted by the rotating wheel media on the mathematics learning outcomes of class V students of SDN 2 Fontein, Kupang City. The type of research used in quantitative research is Pre-Experimental research. The population in this study was class V students of SDN 2 Fontein, totaling 19 students, while the collection technique was tests and documentation. The validity test was calculated using SPSS 2021 with the results of 15 valid questions, the rehabilitation test with an r value = 0.8046 with a very high criterion conclusion, the test of the level of difficulty of the questions was calculated using SPSS 2021 with the conclusion of 10 easy numbers and 5 medium numbers and the test of the question discrimination with the conclusion of 13 good numbers and 2 very good numbers. Hypothesis testing and T-test with SPSS 2021 with sig (2 tailed) t-test for equal variances assumed at 0.000 then the significance value <0.05 means Ho is rejected and Ha is accepted. The results of this study indicate an increase in student learning outcomes that can be seen from the average learning outcomes in the post-test of the experimental class, namely 58.83 and the pre-test of the experimental class, namely 36.47. These results indicate that the post-test learning outcomes of the experimental class are higher than the pre-test learning outcomes of the experimental class. Furthermore, based on the results of data analysis using the hypothesis test T-Tests (Independent Samples Test) above, at the sig. (2-tailed) t-test for Equal variances assumed of 0.000, the significance value <0.05 means that Ho is rejected or Ha is accepted so that it can be concluded that there is a significant influence of the learning media of the rotating wheel of geometric shapes on the mathematics learning outcomes of class V students of SDN 2 Fontein-Kupang City.